2015
DOI: 10.1007/s10519-015-9761-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene–Environment Interplay in Physical, Psychological, and Cognitive Domains in Mid to Late Adulthood: Is APOE a Variability Gene?

Abstract: Despite emerging interest in gene–environment interaction (GxE) effects, there is a dearth of studies evaluating its potential relevance apart from specific hypothesized environments and biometrical variance trends. Using a monozygotic within-pair approach, we evaluated evidence of G×E for body mass index (BMI), depressive symptoms, and cognition (verbal, spatial, attention, working memory, perceptual speed) in twin studies from four countries. We also evaluated whether APOE is a ‘variability gene’ across thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…risk for Alzheimer’s disease is magnified for those with APOE risk alleles who are also obese or have high blood pressure in midlife. Moreover, reports from the IGEMS consortium using a within-pair MZ twin design report small-to-moderate G × E effects across country and gender for cross-sectional measures of BMI, depressive symptoms, cognitive performance 52 as well as grip strength. 53 Furthermore, APOE may partly account for G × E effects for depressive symptoms and spatial reasoning whereby ɛ4 individuals may show less sensitivity to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…risk for Alzheimer’s disease is magnified for those with APOE risk alleles who are also obese or have high blood pressure in midlife. Moreover, reports from the IGEMS consortium using a within-pair MZ twin design report small-to-moderate G × E effects across country and gender for cross-sectional measures of BMI, depressive symptoms, cognitive performance 52 as well as grip strength. 53 Furthermore, APOE may partly account for G × E effects for depressive symptoms and spatial reasoning whereby ɛ4 individuals may show less sensitivity to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Since twins can provide informative designs to investigate G × E effects, a discordant twin design was used as an alternative approach to investigate G × E. We first used a Fisher's test for heterogeneity to test for within-pair difference heterogeneity in MZ twins, which could indicate the presence of G × E (Reynolds et al 2016). This is an agnostic test to identify the presence of a mixture of distributions, rather than one distribution of the within-pair difference.…”
Section: Methodsmentioning
confidence: 99%
“…Reynolds results suggested APOE may represent a variability gene for depressive symptoms and spatial reasoning, but not for BMI (Reynolds et al, 2016). Ihle et al (2012) found no APOE4 -related cognitive effects in children adolescents and young adults, while Heise et al (2011) found a general reduction of fractional anisotropy and increase in mean diffusivity using diffusion tensor imaging in healthy 20-35 and 50-78 y adults, in APOE 4 carriers relative to non-carriers.…”
Section: Mexico City Pediatric Exposure Modelmentioning
confidence: 96%